2004
DOI: 10.1103/physreve.69.061610
|View full text |Cite
|
Sign up to set email alerts
|

Modified cellular automaton model for the prediction of dendritic growth with melt convection

Abstract: A modified cellular automaton (MCA) coupled with a momentum and species transport model has been developed in order to predict the evolution of dendritic morphology during solidification of alloys in the presence of melt convection. In the present model, the cellular automaton algorithm for dendritic growth is incorporated with the transport model, for calculating fluid flow and mass transfer by both convention and diffusion. The MCA model takes into account the effects of the constitutional undercooling and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 53 publications
1
49
0
Order By: Relevance
“…Phase-field models have been developed [223][224][225] and widely used to simulate solidification in the presence of fluid flow [226][227][228][229][230][231][232][233][234][235][236]. Other methods, such as the sharp-interface tracking technique [237][238][239], lattice Boltzmann models [240][241][242][243], cellular automaton techniques [244][245][246] and Monte Carlo simulations [247], have also become available.…”
Section: Dendrite Tip Growthmentioning
confidence: 99%
“…Phase-field models have been developed [223][224][225] and widely used to simulate solidification in the presence of fluid flow [226][227][228][229][230][231][232][233][234][235][236]. Other methods, such as the sharp-interface tracking technique [237][238][239], lattice Boltzmann models [240][241][242][243], cellular automaton techniques [244][245][246] and Monte Carlo simulations [247], have also become available.…”
Section: Dendrite Tip Growthmentioning
confidence: 99%
“…In present study, which is continuation of author's previous work [2], a probabilistic model of nucleation and growth [9] [10] is developed to supplement deterministic model to describe this phenomena in these alloys without recurrence to experimentation. Much research has been carried out previously on modelling and simulation of solidification phenomena in various processes employing cellular automata or modified cellular automata combined with finite element such as modified additive manufacturing (HDMR [11], LAMP [12] on 316L SS [10], two dimensional CAFE [13], cladding [14] [15]), selective laser melting (SLM) using CAFE [14] [15] [16] [17], CAPF, CAFVM [18] and modified CAFE [19] but none has been conducted on the use of cellular automata method on bulk metallic glasses or their composites. On modelling and simulation of bulk metallic glasses themselves; only two studies have been reported [20] [21] but again they are not aimed at explaining microstructure evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the fundamentals of crystal growth kinetics attract numerous research interests [1][2][3][4][5][6][7][8][9] but the understanding of equiaxed crystal growth is inadequate because of the complexity of the process. Basically, the processing of crystal growth relies only on the undercooling, AT, in the liquid, which is given as AT = AT, + AT r + AT C + AT k (1) where AT, , AT r , AT C and AT k are the thermal, curvature, constitutional and kinetic undercooling, respectively.…”
Section: Introductionmentioning
confidence: 99%